DESIGN AND IMPLEMENTATION OF A MATHEMATICAL ENCRYPTION MODEL FOR THE CENTRAL KURDISH FONT BASED ON UNICODE - Ziyad H. Abid Al Jabbar; Zeravan A. Ali; Hanan A. Taher (Science Journal of University of Zakho, 2023)
This research focuses on the development of encryption algorithms for the Kurdish language, specifically tailored to the Kurdish alphabet. With the rapid growth and digital advancements in the Kurdistan Region of Iraq, there is a pressing need for accurate encryption methods that can be applied to Kurdish texts in administration and digital governance. To address this need, a mathematical encryption model is proposed, leveraging the Kurdish central font supported by Microsoft Windows to ensure compatibility between sender and receiver. The model utilizes the Unicode representation of Kurdish letters to calculate offset and mod values accurately. The effectiveness of the proposed model is validated through its implementation using the Caesar cipher method. Computation tasks are performed using Excel, while the encryption system is designed and programmed in C#. Extensive testing of the system with diverse key values demonstrates its high accuracy, achieving a high success rate in encrypting Kurdish texts. This research contributes significantly to the field of encryption for the Kurdish language, providing a scientific framework for further advancements in this area.